Highly sensitive and selective H2S gas sensors based on flower-like WO3/CuO composites operating at low/room temperature - He, Meng; Xie, Lili; Zhao, Xueling; Hu, Xiaobing; Li, Sihan; Zhu, Zhi-Gang (Journal of alloys and compounds, 2019)
The highly sensitive hydrogen sulfide (H2S) gas sensor was developed from a semiconductor composite structure composed of flower-like WO3 microspheres whose surface was modified with CuO nanoparticles. The composites were prepared by a simple two-step hydrothermal method. The morphology and structure of the samples were examined by XRD, SEM, TEM and BET. The sensing properties of the samples on H2S at different operating temperatures were examined, and the performance of WO3/CuO with different molar ratios was also investigated. Gas-sensing tests show that WO3/CuO composites exhibit high response, excellent selectivity and fast response to ppm-level H2S at low operating temperature of 80 °C. Beyond that, WO3/CuO composites with 7:1 M ratio was responsive to 5 ppm H2S at room temperature (28 °C), and its sensitivity could be reached 16. In addition, the gas sensing mechanism of flower-like WO3 microspheres modified with CuO nanoparticles was also thoroughly discussed. The enhanced sensing properties of composites were mainly attributed to the morphology structure and p-n heterojuction between flower-like WO3 and CuO nanoparticles. [Display omitted] •Flower-like WO3/CuO composite was synthesized by a facile two-step hydrothermal method.•Flower-like WO3/CuO composite microspheres could detect H2S gas at room temperature.•Highly sensitive and selective H2S gas sensor with fast response obtained at optimized low operating temperature (80 °C).•The gas sensing mechanism by the formation of p-n junction is thoroughly discussed in the manuscript.